A theoretical and empirical review of psychological factors associated with falls-related psychological concerns in community-dwelling older people. (30th January 2015) - Hughes, C. C.; Kneebone, I. I.; Jones, F.; Brady, B.
ABSTRACT: Background: Four constructs are encompassed by the term "falls-related psychological concerns" (FrPC); "fear of falling" (FOF), "falls-related self-efficacy" (FSe), "balance confidence" (BC) and "outcome expectancy" (OE). FrPC are associated with negative consequences including physical, psychological, and social. Identifying factors associated with FrPC could inform interventions to reduce these concerns. Methods: Sixty-two empirical papers relating to psychological factors associated with FrPC in community-dwelling older people (CDOP) were reviewed. Four levels of evidence were used when evaluating the literature: good, moderate, tentative, and none. Results: Evidence that anxiety predicted FOF, BC, and OE was tentative. Moderate evidence was found for anxiety predicting FSe. Good evidence was found for depression predicting FSe. Moderate evidence was found for depression predicting both FOF and BC. No evidence was found for depression predicting OE. Tentative evidence was found for FSe predicting depression. Good and moderate evidence was found for quality of life (QoL) being predicted by FOF and BC respectively. Tentative evidence was found for FSe predicting QoL. Moderate evidence was found for QoL predicting both FSe and BC. No evidence was found for QoL predicting FOF. Good and moderate evidence was found for activity avoidance/restriction (AA/AR) being predicted by FOF and FSe respectively. Tentative evidence was found for BC and OE predicting AA/AR, as well as for AA/AR predicting FOF. Moderate evidence for activity level (AL) predicting FOF was identified, however the evidence of this predicting FSe and BC was tentative. Evidence for FOF, FSe, and BC predicting AL was tentative as was evidence to suggest FOF predicted coping. Conclusions: Mixed evidence has been found for the association of psychological factors in association with FrPCs. Future research should employ theoretically grounded concepts, use multivariate analysis and longitudinal designs.